Debreu's Coefficient of Resource Utilization, the Solow Residual, and TFP: The Connection by Leontief Preferences - Thijs ten Raa (European Regional Science Association (ERSA), 2003)
Debreu's coefficient of resource allocation is freed from individual data requirements. The procedure is shown to be equivalent to the imposition of Leontief preferences. The rate of growth of the modified Debreu coefficient and the Solow residual are shown to add up to TFP growth. This decomposition is the neoclassical counterpart to the frontier analytic decomposition of productivity growth into technical change and efficiency change. The terms can now be broken down by sector as well as by factor input.
Keywords: 330